The Effect of Emotional Intelligence on Audit Quality - Andre Kalpin Saragih; Rapina Rapina (International Journal of Entrepreneurship, Business, and Creative Economy, 2022)
Background - The implementation of Community Activity Restrictions or PPKM is one of the efforts to prevent the spread of the Coronavirus. This makes independent auditors have to be able to complete their duties even though they are working from home. Objectives - This study has the objective to examine and test whether or not there is an influence of the independent variable (emotional intelligence) on the dependent or dependent variable (audit quality). Design/Methodology - This study uses primary data by distributing questionnaires using the snowball sampling method. The populations of this study are auditors who work in public accounting firms in Jakarta and Bandung, while the sample in this study is 44 auditors in public accounting firms in Jakarta and Bandung. Hypothesis testing using simple linear analysis with SPSS Version 26. Findings - This study found that emotional intelligence has an effect on audit quality; namely, when emotional intelligence increases, audit quality also increases. The emotional intelligence of the auditor is able to influence the quality of the audit seen by the auditors who work in public accounting firms. Research Limitations - Furthermore, one of the problems in this study is the limited time in distributing questionnaires; the researchers only took samples in the cities of Jakarta and Bandung. Originality/Value - This research was conducted to convey information as well as input for the development of knowledge in the field of auditing in Indonesia, especially in improving audit quality, and to provide empirical evidence on the effect of emotional intelligence on audit quality.